Caring for The Elderly: A Comparative Review and Policy Implications for Nutritional Fulfillment - Ameylia Puspita Rosa Dyah Ayu Arintyas; Raihan Chaerani Putri Budiman (Universitas Negeri Gorontalo, 2025)
As individuals age, physiological changes increase the risk of malnutrition, making proper nutrition essential for maintaining health and preventing chronic diseases such as diabetes and hypertension. This study aims to examine the effectiveness of elderly nutrition programs in Indonesia, particularly the Pemberian Makanan Tambahan (PMT) and Posyandu Lansia initiatives, and to compare them with similar approaches in Thailand, Singapore, Malaysia, and the United States. A qualitative research method was employed using a case study approach focused on the in-depth analysis of policies and program implementation in Indonesia, supported by international comparative literature. Findings indicate that Indonesia’s community-based programs face significant challenges, including low awareness, limited resources, unequal access in rural areas, and social stigma toward the elderly. Comparisons with other countries reveal that successful programs rely on integrated policy frameworks, availability of trained professionals, technological innovation, and sustainable funding. This study highlights the importance of collaboration among government, healthcare providers, and communities, as well as the need for multisectoral strategies to ensure equitable and sustainable access to elderly nutrition services. The findings offer policy recommendations to strengthen nutrition systems for the elderly through improved governance, increased nutrition literacy, and more inclusive service delivery models